Distribution and correlation of Sabellidites cambriensis (Annelida?) in the basal Cambrian on Baltica - Ebbestad, Jan Ove R.; Hybertsen, Frida; Högström, Anette; Jensen, Sören; Palacios, Teodoro; Taylor, Wendy L.; Agic, Heda; Høyberget, Magne; Meinhold, Guido (Geological Magazine, 2021)
Sabellidites cambriensis is a tubular non-mineralized metazoan that appears as compressed ribbon-shaped imprints with transverse wrinkling, thick walls and an even tube diameter of up to 3 mm. The distribution of Sabellidites is investigated in three Ediacaran–Cambrian sections on the Digermulen Peninsula in Arctic Norway, spanning the Manndrapselva Member of the Stáhpogieddi Formation and the lower member of the Breidvika Formation. Here, the Ediacaran–Cambrian boundary is located in the lower part of the upper parasequence (third cycle) of the Manndrapselva Member. Specimens of Sabellidites are rare but consistently present close to the lowest level of Treptichnus pedum and upsection, whereas the taxon is common and abundant in the lower part of the lower member of the Breidvika Formation, with an upper record at c. 55 m above the base. The range is comparable with that of the GSSP section in Newfoundland, Canada, establishing Sabellidites as an index fossil for the lowermost Cambrian. In the Manndrapselva Member, Sabellidites co-occurs with the acritarch Granomarginata, indicative of the lowermost Cambrian Granomarginata Zone, whereas in the Breidvika Formation it co-occurs with Asteridium. Sabellidites is widely distributed in Baltica, through the Rovnian and Lontovan regional stages but confined to the Fortunian global stage. In its lower range, Sabellidites is associated with a Treptichnus pedum trace fossil association and a depauperate leiosphaerid acritarch assemblage, followed by a Granomarginata assemblage. In its upper range, Sabellidites co-occurs with acritarchs of the Asteridium–Comasphaeridium Zone and the tubular foraminiferan Platysolenites. In Baltica, Sabellidites is a useful index fossil.